The Impact of Coagulation Biomarkers on Survival Outcomes in Adult Glioblastoma - Rahmi Atıl Aksoy; Timur Koca; Yasemin Şengün; Ece Atak; Aylin Fidan Korcum (Medicina)
Background and Objectives: Glioblastoma presents a significant challenge in oncology due to its aggressive nature and poor prognosis, despite advancements in treatment. This study aims to comprehensively evaluate the prognostic significance of coagulation biomarkers, including the novel albumin/D-dimer ratio, in adult glioblastoma patients. Material and Methods: This retrospective study included 74 adult glioblastoma patients who underwent Stupp protocol treatment. Blood samples were collected before radiotherapy to measure biomarkers, including prothrombin time (PT), activated partial thromboplastin time (aPTT), albumin, D-dimer, and the albumin/D-dimer ratio. The prognostic significance of these biomarkers for progression-free survival (PFS) and overall survival (OS) was assessed using both univariate and multivariate Cox regression analyses. Results: The median follow-up time was 12.2 months (range, 1–77.4 months). Univariate analysis revealed that ECOG performance status (p = 0.001), D-dimer (p = 0.03), and albumin (p = 0.001) were significant prognostic factors for PFS. Multivariate analysis identified albumin (p = 0.02) as an independent prognostic biomarker for PFS. For OS, univariate analysis showed that age (p = 0.004), ECOG performance status (p = 0.001), tumor volume (p = 0.007), extent of resection (p = 0.01), radiotherapy dose (p = 0.001), D-dimer (p = 0.02), albumin (p = 0.001), albumin/D-dimer ratio (p = 0.02), and PT (p = 0.002) were significant prognostic factors. Multivariate analysis revealed age (p = 0.04), extent of resection (p = 0.02), and PT (p = 0.04) as independent prognostic factors for OS. Conclusions: Our findings highlight the prognostic significance of coagulation biomarkers, particularly PT, D-dimer, albumin, and the albumin/D-dimer ratio, in glioblastoma. These biomarkers may serve as valuable tools for prognostic assessment and personalized treatment strategies, warranting further exploration in larger prospective studies.